Application of COBIT 5 for Hospital Services Management Information System Audit - Leo Mahadya Suta, Ida Bagus; Surya Mahendra, I Gusti Ngurah Agung; Sudarma, Made (International Journal of Engineering and Emerging Technology; Vol 3 No 2 (2018): July - December, 2019)
We conduct research on hospital management information system management audits where management includes services to patient queuing times and medical personnel who implement COBIT 5 with the Deliver, Service, Support (DSS) domain from the results of the application of DSS domains on COBIT 5 then maturity levels are obtained an average of 2.2 to 2.8 who have an IT governance process in hospital services has a pattern that is repeatedly performed